Influence of Adansonia digitata leaves dye extraction solvent nature on the structural and physical properties of biosynthesized ZnO nanoparticles. (2021) - Kane, A.O.; Ngom, B.D.; Sakho, O.
Abstract: We report on the synthesis ZnO nanoparticles with Andasonia digitata leaves extract using different extraction solvents: ethanol, methanol, acetone and propanol. The influence of the solvent extraction nature was studied using the characterizations techniques: DRX, BET, SEM, TEM, RAMAN. The results showed the nanoparticles obtained with the solvent Methanol are the best with spherical nanoparticles of sizes around 20 nm with fewer defects and good dispersion compared to those obtained with the other solvents.